The Static Eccentricity Fault Diagnosis in Time Domain at Line Start Permanent Magnet Synchronous Motor - Zafer Dogan (Journal of New Results in Science)
Recently, Line Start Permanent Magnet Synchronous Motor have been commonly utilized in industrial areas because of their high efficiency. Motor faults during operation cause losses of production and high maintenance and repair expenditures. In this study, the effect of static eccentricity fault on line start permanent magnet synchronous motor was investigated. The simulation models of motor belonging to healthy and fault status were formed via Finite Elements Method. The analyses in time domain of motor currents under different load conditions were carried out by using these models. When the results of the analyses were investigated, the motor fault was successfully diagnosed via the recommended method.